With Nansen in the North A Record of the Fram Expedition in 1893–96 - Johansen, Hjalmar 1867-1913 (Cambridge library collection. Polar Exploration, 1899)
Fredrik Hjalmar Johansen (1867–1913) was a Norwegian Polar explorer. He accompanied Nansen on the Fram Expedition of 1893–6 and took part in a number of explorations of the Svalbard archipelago. He later participated in Roald Amundsen's expedition to the South Pole in 1910–12, although he was written out of the official history following a bitter dispute with Amundsen. Johansen's account of Nansen's Fram Expedition appeared in Norwegian in 1898, and this English translation was published the following year. It describes Nansen's attempt to drift north in a deliberately ice-bound ship and then ski to the North Pole, and reveals the dangers and challenges faced by the crew during their three-year journey. Although they did not reach the Pole, they set a new furthest-north record that stood for several years. Nansen's own account of the expedition, Farthest North, is also available as part of the Cambridge Library Collection